Alternative LIM homeodomain splice variants are dynamically regulated at key developmental steps in vertebrates. Issue 7 (18th March 2022) - Wheaton, Benjamin Joel; Häggström, Sara Lea; Muppavarapu, Mridula; González‐Castrillón, Luz María; Wilson, Sara Ivy
Abstract: Background: Alternative splicing provides a broad strategy to amplify the genome. Yet how alternative splicing influences neurodevelopment or indeed which variants are translated at developmental choice points remains poorly explored. Here we focused on a gene important for neurodevelopment, the Lim homeodomain transcription factor, Lhx9. Lhx9 has two noncanonical splice variants, Lhx9a and Lhx9b which compared with the canonical variant Lhx9c have a truncated homeodomain and an alternative C‐terminal sequence, suggesting that, if translated, these variants could differently impact on cellular function. Results: We created a unique antibody tool designed to selectively detect noncanonical Lhx9 variants (Lhx9ab) and used this to examine the protein expression dynamics in embryos. Lhx9ab variants were translated and dynamically expressed similarly between mouse and chicken at key developmental choice points in the spinal cord, limbs and urogenital ridge. Within the spinal cord, enrichment of Lhx9c vs Lhx9ab expression was observed during key migration and axonal projection choice points. Conclusions: These data support the notion that the expression dynamics between canonical and noncanonical Lhx9 variants could play an important role in spinal neuron maturation. More broadly, determining the temporal dynamics of alternative protein variants is a key entry point to understand how splicing influences developmental processes. Key Findings: The LIM homeodomain transcription factor Lhx9, which is important for neural development has two non‐canonical splice variants, Lhx9a and Lhx9b which compared with the canonical variant Lhx9c have a truncated homeodomain and alternative C‐terminal sequence. An antibody was created which selectively recognises the non‐canonical Lhx9 spice variants (Lhx9ab) which was used to determine the spatiotemporal expression of non‐canonical Lhx9 variants during mouse and chicken embryogenesis. It was discovered that Lhx9ab non‐canonical variants were translated and detected at key developmental choice points in the spinal cord, urogenital ridge and limbs in a partly overlapping and partially independent manner to Lhx9 canonical transcripts. Within the spinal cord, Lhx9ab protein was detected in dI1 neurons at key choice divergence points for dI1c and dI1i neural projections suggesting that the expression dynamics between canonical and non‐canonical Lhx9 variants could play an important role at key development choice points within the spinal cord. More broadly, determining the temporal dynamics of alternative protein variants is a key entry point to understand how splicing influences developmental processes.